Pleasure and Mind - Škuljević, Željko (Pregled: časopis za društvena pitanja / Periodical for social issues, 2010)
Despite the title’s strong allusion to Epicurus, his hedonism will be discussed somewhat later; we will begin with Plato’s Philebus: what is Good and how should people live if they wish to achieve that notion (engaged in dialogue discussing this issue are Socrates, Philebus and Protarchus).